ESPAçO URBANO: DO ACESSO PELOS DIREITOS FORMAIS À COERçãO VELADA DA PARTICIPAÇÃO POLÍTICA FEMININA - Nabozny, Almir (UFPR, 2007)
This article discusses the social relations of gender and productionof space, with emphasion the female political participationas a way to push access to the city. It is discoursing on thewomen in different social roles in their insertion and participationin politics, this article is divided in four parts. After a briefintroduction to the theme, follows an object approximation, themethodological base is based on empiric work, which is theorigin of the article. The female social relations, their potentialsand limits are illustrated by quotations from the empiricismabout the woman participation in the “Orçamento Participativo”(Participative Budget) in the city of Ponta Grossa, state of Paraná(Brazil). The following part presents the political developmentby women front of their roles of gender assumed and constructedsocially. The last considerations are an emphasis onthis introspection that influences the female actuation in publicand private space.